Assessment of Partial Edentulism Based on Kennedy’s Class IV Classification- Retrospective Study - Cibikkarthik T1 , Revathi Duraisamy2 , Jessy P3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Kennedy’s classification provides immediate visualization, recognition of prosthesis support and assessmentof design features of removable partial denture. Missing Teeth in patients with the long span Kennedy class IVsituation demands biomechanical balance and aesthetic improvement. The long-span condition complicatesthe problem because of the unavailability of sufficient number of abutments to support the prosthesis.Conventional removable prosthesis and fixed partial denture are not advised for the same reason. The systemof classifying the partially edentulous arch would be an enormous aid in providing a precise word pictureof a particular dental arch that is to be discussed. Aim was to determine the prevalence of Kennedy’s classIV classification among the partial edentulous patients residing in chennai who had undergone treatment forthe replacement of missing tooth in the department of Prosthodontics,saveetha dental college,chennai,India.Study samples of 1341 cases were obtained from the data of 86000 patients between June 2019 and March2020. Statistical software used for analysis was the SPSS(statistical package for the social sciences) whichis designed by IBM and the statistical tests used were frequency tables along with bar graphs to analyse andcompare the obtained results. The results showed that the patients with Kennedy’s class IV were found tobe the most prevalent in the male population. The findings of the present study showed that Prevalence ofpartial edentulism based on Kennedy’s class IV was commonly occuring in the male population and alsoreveals that lower arch has a higher incidence of Kennedy’s class IV.